Experimental data on Helically Coiled Oscillating Heat Pipe (HCOHP) design and thermal performance - Yeboah, Siegfried K.; Darkwa, Jo (2020)
Experimental and derived data from three Helically Coiled Oscillating Heat Pipes (HCOHPs) charged with ethanol, methanol and deionized water working fluids respectively are presented. The data was obtained from prototypes of the HCOHPs fabricated out of copper and tested under laboratory conditions. The primary data presented covers the HCOHP aspects, charging of the working fluid and temperature measurements from Omega K-type Thermocouples installed on the evaporators, condensers, adiabatic sections, and on the cylindrical copper vessel integrated with it. The derived data covers the HCOHPs performances and thermal contact resistance experienced during laboratory testing. The data on the aspects and charging of the working fluid provides useful information for the validation of design parameters of other heat pipes. The measured temperature data and the derived performance data can used to validate the performance of heat pipes in other studies and to depict performance profiles in standard text and reference books. The nature of the data presented as a whole would be useful for comparative analysis involving heat pipes and other passive heat transfer devices.